Evolution of sine-Gordon equation kinks in the presence of spatial perturbations - Ekomasov, E.G.; Shabalin, M.A.; Azamatov, Sh.A.; Buharmetov, A.F. (Functional Materials, 2006)
Using numerical methods, the influence of damping, external power and spatial modulations of parameters on Kinks of the modified sine-Gordon equation is investigated. Changes of the kink structure, velocity and width at the moment of intersection of localization field of the spatial modulations of parameters have been studied.